Hubungan Interdependensi Indonesia-China di Tengah Ketegangan Laut Natuna Utara - Ahmad Naufal Farras (Indonesian Perspective, 2023)
Relations between Indonesia and China have existed for more than 70 years. Throughout the history of relations between the two countries, there have been ups and downs. In 1967 Indonesia suspended diplomatic relations with China. It took Indonesia 23 years to re-open diplomatic relations with China. Furthermore, Indonesia and China began to build a more cooperative relationship. However, in 2009 tensions resurfaced after China claimed unilaterally that the North Natuna Sea was part of China based on their historical maps. Interestingly, even though there were territorial disputes, Indonesia and China continued to cooperate. This study aims to analyze the reasons why Indonesia has continued to maintain cooperative relations with China until now, even though Indonesia is in an unfavorable position in the dispute over the North Natuna Sea area. This study uses the theory of interdependence by Nye which is then analyzed using qualitative research methods. This article argues that the mechanism of economic cooperation will increase the common security and stability in the region.